Shroom: A Cultural History of the Magic Mushroom - Yamin‐Pasternak, Sveta (Ethnobiology Letters, 2010)
Review of Shroom: A Cultural History of the Magic Mushroom. Andy Letcher. 2007. Ecco HarperCollins, New York. Pp. 384. 14.99 (paperback). ISBN 9780060828295.